Cognitive Rehabilitation Improves Memory and Distress Tolerance in Social Anxiety Disorder: A Quasi-Experimental Study - Jahanfar, Hoda; Khajeh Ahmad Attari, Mohammad Amin; Dasht Bozorgi, Zahra (Shahroud Journal of Medical Sciences, 2025)
Background: Social Anxiety Disorder (SAD) is a prevalent mental health condition that can substantially impair an individual's quality of life. This study investigates the efficacy of cognitive rehabilitation interventions in ameliorating memory deficits, enhancing distress tolerance, and promoting psychological health among individuals diagnosed with SAD.Methods: This quasi-experimental study utilized a pretest-posttest control group design. The target population consisted of individuals diagnosed with SAD who sought treatment at counseling and psychological service centers in Ahvaz during 2023. A convenience sample of 30 participants, meeting pre-defined inclusion criteria, was recruited. Participants were then randomly assigned to either the experimental (n=15) or control (n=15) group. The experimental group received ten 90-minute sessions of cognitive rehabilitation. The control group received no intervention during the study period. The Retrospective and Prospective Memory Questionnaire (RPMQ), Distress Tolerance Scale (DTS), and Symptom Checklist-25 (SCL-25) served as the assessment instruments. Data were analyzed using analysis of covariance (ANCOVA) conducted in SPSS.Results: The results demonstrated that cognitive rehabilitation significantly improved retrospective memory (F=341.81, P-value<0.001), prospective memory (F=156.43, P-value<0.001), distress tolerance (F=285.75, P-value<0.001), and psychological health (F=180.11, P-value<0.001) in the sample of individuals with SAD.Conclusions: This study strongly supports the efficacy of cognitive rehabilitation for improving key domains in SAD. Significant improvements in retrospective memory, distress tolerance, and psychological health suggest its therapeutic value for this multifaceted disorder, adding to the growing body of literature on cognitive rehabilitation for anxiety disorders.